Socialization and violence: Introduction and framework. (September 2017) - Checkel, Jeffrey T
This article sets the stage for a special issue exploring group-level dynamics and their role in producing violence. My analytic focus is socialization, or the process through which actors adopt the norms and rules of a given community. I argue that it is key to understanding violence in many settings, including civil war, national militaries, post-conflict societies and urban gangs. While socialization theory has a long history in the social sciences, I do not simply pull it off the shelf, but instead rethink core features of it. Operating in a theory-building mode and drawing upon insights from other disciplines, I highlight its layered and multiple nature, the role of instrumental calculation in it and several relevant mechanisms – from persuasion, to organized rituals, to sexual violence, to violent display. Equally important, I theorize instances where socialization is resisted, as well as the (varying) staying power of norms and practices in an individual who leaves the group. Empirically, the special issue explores the link between socialization and violence in paramilitary patrols in Guatemala; vigilantes in the Bosnian civil war; gangs in post-conflict Nicaragua; rebel groups in the Democratic Republic of Congo, El Salvador, Sierra Leone and Uganda; post-conflict peacekeepers; and the US and Israeli military. By documenting this link, we contribute to an emerging research program on group dynamics and conflict.